Glucose metabolism in mammalian photoreceptor inner and outer segments. (17th May 2017) - Narayan, Daniel S; Chidlow, Glyn; Wood, John PM; Casson, Robert J
Abstract: Photoreceptors are the first‐order neurons of the visual pathway, converting light into electrical signals. Rods and cones are the two main types of photoreceptors in the mammalian retina. Rods are specialized for sensitivity at the expense of resolution and are responsible for vision in dimly lit conditions. Cones are responsible for high acuity central vision and colour vision. Many human retinal diseases are characterized by a progressive loss of photoreceptors. Photoreceptors consist of four primary regions: outer segments, inner segments, cell bodies and synaptic terminals. Photoreceptors consume large amounts of energy, and therefore, energy metabolism may be a critical juncture that links photoreceptor function and survival. Cones require more energy than rods, and cone degeneration is the main cause of clinically significant vision loss in retinal diseases. Photoreceptor segments are capable of utilizing various energy substrates, including glucose, to meet their large energy demands. The pathways by which photoreceptor segments meet their energy demands remain incompletely understood. Improvements in the understanding of glucose metabolism in photoreceptor segments may provide insight into the reasons why photoreceptors degenerate due to energy failure. This may, in turn, assist in developing bio‐energetic therapies aimed at protecting photoreceptors.